2023
DOI: 10.1021/acs.langmuir.3c01238
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Dynamics along the Chain Contours of Polymer-Grafted Nanoparticles

Abstract: Densely grafted polymer chains onto spherical nanoparticles produce a diverse range of conformations. At high grafting densities, the corona region near the nanoparticle surface undergoes intense confinement due to a high concentration of chains in the concentrated polymer brush (CPB) region, which results in strong stretching for portions of the chains located within. In contrast, a semi-dilute polymer brush (SDPB) forms farther away from the core and offers reduced confinement for the polymer and more ideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Further, assuming b = 1.28 for Kremer−Grest chains, 35,69 we estimate that ν̃= 0.28 from the slope of a linear fit to the data. This effective ν̃is close to the value ν̃= 0.30 estimated from experiments 34 and simulations, 48 and it suggests that the chains are strongly stretched on length scales below R i* due to the confinement imposed by their neighbors. Hence, our results indicate that the observed inflection in the MSDs is indicative of confined chain dynamics near the NP surface, and its presence delineates between the CPB-and SDPB-like regimes predicted by theory.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…Further, assuming b = 1.28 for Kremer−Grest chains, 35,69 we estimate that ν̃= 0.28 from the slope of a linear fit to the data. This effective ν̃is close to the value ν̃= 0.30 estimated from experiments 34 and simulations, 48 and it suggests that the chains are strongly stretched on length scales below R i* due to the confinement imposed by their neighbors. Hence, our results indicate that the observed inflection in the MSDs is indicative of confined chain dynamics near the NP surface, and its presence delineates between the CPB-and SDPB-like regimes predicted by theory.…”
supporting
confidence: 83%
“…The relaxation time of monomers varies non-monotonically with monomer position, with monomers near the chain center exhibiting the slowest relaxations. , Additionally, the intrachain relaxations of grafted polymers do not follow simple exponential decays. ,, Instead, neutron spin–echo (NSE) measurements find that grafted chains are confined by their neighbors and do not fully relax on observable time scales. , By selectively contrast matching the grafted chains, NSE measurements reveal that dynamics are slower in the CPB region than in the SDPB region of a long brush . This behavior was confirmed in recent molecular dynamics (MD) simulations, which also showed that the relaxation time of individual chains increases with increasing confinement (i.e., increasing σ). , Although these investigations suggest that the relaxations of grafted polymers are affected by the local brush structure, a direct connection between the brush structure and dynamics has not yet been demonstrated.…”
mentioning
confidence: 89%
See 3 more Smart Citations